Implementasi Aplikasi Sistem Pengamanan Smarthome menggunakan Face Recognition Berbasis ESP32 - Lemuel, Jason; Birowo, Sigit (Jurnal Informatika dan Bisnis, 2025)
In this advanced digital age, with the many advances in digital technology and its increasing adoption along with the pace of globalization bringing a large and fast-paced economy, however, all that changed after the spread of the COVID-19 pandemic, where after the economic slowdown drastically caused all aspects of people's lives to also change drastically, all of this indicates how important it is for digitalization to be adopted in every layer of people's lives. Smart home is a combined application of technology and services that are specialized in the home environment with certain functions aimed at increasing security, efficiency and comfort, smart home includes a digital-based security system that adds a level of security in the neighborhood with greater reliability in guarding the entrance. This field research (Qualitative Method) that uses unstructured interviews, observation, literature study, and documentation. As a data collection technique this unstructured interview is from the family. The system development method is based on information obtained from interviewee. The smart door lock in smart home system detects human faces caught by the camera, then compares the face with the one that has been registered before if the same then it will be given access by opening the lock for 20 seconds otherwise it will continue to lock with RGB lights turning red indicating that the person is not recognized by the system, The system can be controlled by a web application that can be accessed using a computer or cellphone. This research is to make a smart home security system to using ESP32 to regulate door access which aims to eliminate human error in maintaining environmental security.